(untitled) (Economic and Political Thought, 2017)
Summary This article deals with estimates of the costs of the informal legal aid system in Poland along with estimates of a possible institutional reform of the system. Due to the lack of official data it was necessary to apply novel procedures of measurement. Two approaches were used: a quasi-market and a quasi-budget one. In line with the first approach the costs of the informal legal aid system in 2012 were estimated at 540 million PLN. Under the other approach, depending on data availability on particular legal aid providers, three specific procedures of measurement of unit costs were employed, which in combination with precise information on the total number of legal aid providers by type, enabled estimation of the total costs of the informal system. Implementation of the quasi-budget approach resulted in the estimation of the annual total costs of the present system at the level of 514 million PLN (ca 170 million USD). Such a result is thus close to the quasi-market estimate, which seems to raise the credibility of the performed computations. Finally, one is allowed to formulate a conclusion that annual cost of the functioning of the informal system of legal aid in Poland was well above 500 million PLN, as the calculus was carried out with minimalistic cost assumptions. The article also attempts at estimating the costs of an institutionalised legal aid reform in Poland. A main premise behind adequate computations is the observation that the new system will not replace the existent one but will just supplement it. This is so because a complete replacement of the present informal system with a new formal one would prove economically ineffective as this act would be tantamount to depriving the already well-functioning providers of the right to give legal support to those in need. A key issue for estimating the costs of the reform consists in establishing the amount of unmet demand for legal aid as well as the outflow of legal aid recipients from the old to the new system, including outflows from the commercial sector of legal advice. Using deductive analysis, supported by data and conclusions drawn on the basis of the national questionnaires into legal aid recipients and providers, the upper estimate of the total costs of the reform was fixed at the level slightly below 180 million PLN (ca 60 million USD).